Updating the NLRC4 Inflammasome: from Bacterial Infections to Autoimmunity and Cancer - Wen, Jiexia; Xuan, Bin; Liu, Yang; Wang, Liwei; He, Li; Meng, Xiangcai; Zhou, Tao; Wang, Yimin (Frontiers in Immunology, 2021)
Inflammasomes comprise a family of cytosolic multi-protein complexes that modulate the activation of cysteine-aspartate-specific protease 1 (caspase-1) and promote the maturation and secretion of interleukin (IL)-1β and IL-18, leading to an inflammatory response. Different types of inflammasomes are defined by their sensor protein which recognizes pathogenic ligands and then directs inflammasome assembly. Although the specific molecular mechanisms underlying the activation of most inflammasomes are still unclear, NLRC4 inflammasomes have emerged as multifaceted agents of the innate immune response, playing important roles in immune defense against a variety of pathogens. Other studies have also expanded the scope of NLRC4 inflammasomes to include a range of inherited human autoimmune diseases as well as proposed roles in cancer. In this review article, we provide an updated overview of NLRC4 inflammasomes, describing their composition, activation mechanisms and roles in both microbial infections and other disease conditions.